Tourism and Gross Domestic Product short-run causality revisited: A symbolic transfer entropy approach. Issue 1 (February 2023) - Camacho, Maximo; Romeu, Andres
We employ a symbolic transfer entropy panel data test in a large-scale data set to provide new insights on the worldwide short-term causality relations between growth and inbound tourists. Using a large data set on 145 countries from the World Bank Open Data website, we show that, despite the evidently strong correlation between these two magnitudes, claiming that the increases in inbound tourists Granger-cause positive shocks in GDP is not supported by the data. By contrast, the data seem to point out in the direction of a reverse causality in that it is GDP growth what drives international inbound tourists in the short run. JEL classification: C12, C14, C33, C55.